Biosorption of chromium and the morphological effects on oscillatoria willei. - Morales, Merari S. 4 0 16; 5 (2006)
u
Thesis (B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2006.
Keywords: 2 -- 0; 6; 20; 20; 2